Quantifying and Comparing the Match Demands of U18, U23, and 1ST Team English Professional Soccer Players - Reynolds, James; Connor, Mark; Jamil, Mikael; Beato, Marco (Frontiers in Physiology, 2021)
The aim of this study was to quantify and compare the match load demands of U18, U23 and 1ST team players during the official season. A total of 65 matches and 495 (U18 = 146, U23 = 146, 1ST team = 203) individual player game observations were included in this analysis. A 10 Hz GNSS system and 100 Hz triaxial accelerometer (STATSports, Apex, Northern Ireland) were used to monitor the following metrics during official matches: total distance, high-speed running (HSR), sprint distance, high metabolic distance, explosive distance, high-intensity bursts distance, speed intensity and dynamic stress load (DSL) were analyzed. A MANOVA test reported significant (p < 0.001) differences among the groups. HSR during matches was lower (d = small) for U18 players than the U23 and 1ST team players. Sprint distance and high-intensity bursts distance were lower (small) in U18 compared to the U23 and 1ST team. DSL was greater in 1ST compared to U18 (small) and U23 (small). This study reported that the differences between groups were greater for HSR, sprint distance, high-intensity bursts distance, and DSL, while total distance, high metabolic load distance, explosive distance and speed intensity did not differ between the groups. These findings could be used to design training programs in the academy players (i.e., U18) to achieve the required long-term physical adaptations that are needed to progress into the U23 and 1ST teams.